2014
DOI: 10.3390/molecules19021976
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolidine-Mediated Direct Preparation of (E)-Monoarylidene Derivatives of Homo- and Heterocyclic Ketones with Various Aldehydes

Abstract: An efficient method for the facile synthesis of (E)-monoarylidene derivatives of homo-and heterocyclic ketones with various aldehydes in the presence of a pyrrolidine organocatalyst has been achieved. A range of α,β-unsaturated ketones were obtained in moderate to high yields (up to 99%). Unlike the Claisen-Schmidt condensation process, the formation of undesired bisarylidene byproducts is not observed. The possible reaction mechanism suggests that the reaction proceeds via a Mannich-elimination sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 42 publications
1
4
0
5
Order By: Relevance
“…Compound 4 was prepared according to Typical procedure 1 from ( E )-3-benzylideno-1-metylopiperyd-4-one (0.392 g, 1.95 mmol) [ 55 ] and ( E )-cinnamoyl cyanide (0.346 g, 2.2 mmol) [ 25 ] and purified by flash column chromatography (AcOEt:Hex, 30:70) to yield a pink solid (0.588 g, 91%).…”
Section: Methodsmentioning
confidence: 99%
“…Compound 4 was prepared according to Typical procedure 1 from ( E )-3-benzylideno-1-metylopiperyd-4-one (0.392 g, 1.95 mmol) [ 55 ] and ( E )-cinnamoyl cyanide (0.346 g, 2.2 mmol) [ 25 ] and purified by flash column chromatography (AcOEt:Hex, 30:70) to yield a pink solid (0.588 g, 91%).…”
Section: Methodsmentioning
confidence: 99%
“…1 H NMR (500 MHz, chloroform-d) δ 6.68 (t, J = 7.5 Hz, 1H), 4.51 (s, 2H), 3.96 (t, J = 6.1 Hz, 2H), 2.53 (t, J = 6.1 Hz, 2H), 2.03 (p, J = 7.5 Hz, 2H), 1.03 (t, J = 7.5 Hz, 3H). 13 (13); 41 (31); 42 (18); 43 (16); 53 (33); 54 (17); 55 (52); 56 (19); 66 (12); 67 (43); 68 (14); 69 (15); 81 (13); 83 (100); 84 (14); 95 (15); 97 (12); 111 (11); 112 (51); 140 (7) [M] + . Anal…”
Section: -Propylidenedihydro-2h-pyran-4(3h)-one (4eb)unclassified
“…1 H NMR (500 MHz, DMSO-d 6 ) δ 7.47 (s, 6H), 4.61 (s, 2H), 3.69 (s, 2H), 2.58 (t, J = 6.3 Hz, 2H), 1.50−1.17 (m, 9H). 13 (42); 42 (18); 43 (13); 44 (16); 53 (10); 55 (12); 56 (18); 57 (100); 67 (14); 81 (38); 96 (16); 109 (29); 122 (11); 137 (18); 139 (14); 166 (16); 183 (31); 239 (6) [M] + . Anal (16), 41 (100), 42 (25), 43 (45), 44 (30), 51 (12), 53 (28), 55 (35), 56 (30), 57 (83), 65 (15), 67 (28), 68 (13), 77 (29), 78 (10), 79 (36), 80 (21), 81 (25), 82 (98), 83 (14), 91 (24), 93 (18), 94 (13), 95 (10), 97 (10), 98 (15), 99 (13), 107 (12), 108 (15), 109 (10), 110 (26), 111 (10), 121 (12), 122 (19), 135 (15), 136 (11) tert-Butyl 3-Benzylidene-5-methyl-4-oxopiperidine-1-carboxylate (4jf).…”
Section: Tert-butyl 3-(cyclohexylmethylene)-4-oxopiperidine-1-carboxy...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, literature search revealed that synthetic methodologies that can be applied to the preparation of 3-alkylidenetetrahydropyran-4-ones 1 with diverse substitution patterns are limited. There are several methods which enable the introduction of arylidene group onto the plain tetrahydropyran-4-one ring using a reaction with aromatic aldehydes in the presence of catalytic amount of TMSNMe 2 and MgBr 2 Et 2 O [7] or pyrrolidine [8]. There are also two literature reports which describe preparation of specific 3-methylidenetetrahydropyran-4-ones, and thus 8-methylidene-9oxo-6-oxaspiro [5,6] decane was prepared by carbocyclization of unsaturated thioesters under palladium catalysis [9] and 2-butyl-6,6-dimethyl-3-methylidenetetrahydropyran-4-one was obtained in a three-step reaction sequence starting from 6-ethoxy-2-methyl-5-diphenylphosphorylhex-3-yn-5-en-2-ol [10].…”
Section: Chemistrymentioning
confidence: 99%